Evaluation of Asthma Pharmacotherapy and Treatment Outcome Among Asthmatic Patients Undergoing Follow-Up At The Chest Clinic At AUSH (Ambo University Specialized Hospital), Oromia Region, West, Ethiopia - Takele Achalu Dengela; Sorato, Mende Mensa (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2022)
Asthma prevalence is rising all over the world. Poor asthma control, which is linked to more frequent asthma symptoms and bronchodilator usage, worse pulmonary function, higher reliance on emergency medical services, and more functional impairment, appears to be a contributing factor to the worldwide burden of asthma. The morbidity and mortality associated with asthma continue to be under-treated, despite the development of new medications and evidence-based recommendations in recent years. Background: Methods: In order to evaluate the effectiveness of asthma pharmacotherapy, prescriber adherence to evidence-based recommendations and factors associated with treatment outcomes among asthmatic patients on follow-up at Ambo University Specialized hospital, chest clinic, Oromia region, west Ethiopia, a retrospective cross-sectional study was conducted. To choose study participants for this investigation, a systematic random sampling technique was adopted. Using the Windows version of SPSSv16, descriptive analysis was carried out. Result: 106 (50.50%) of the 210 asthmatic patients who were investigated were female, with a mean age of (43.2513.6) years. When it comes to anti-asthmatic medications, short-acting Beta2-agonists account for 63.80% of prescriptions (salbutamol puffs account for 34.09% and oral salbutamol for 27.91%), while inhaled corticosteroids only make up 15.58%. Short-acting Beta2-agonist plus prednisolone, which 39.57% of asthmatic patients used, was the most anti-asthmatic medication combination. About 56.2% of asthma sufferers had their asthma under bad control. Social drug usage and treatment outcomes are related (p-value = 0.031). Conclusion: Low asthma control rates were observed. Antibiotics were given to more than half of the patients to treat upper and lower respiratory infections as well as urinary tract infections. Less than half of the patients took inhaled corticosteroids. Long-acting beta 2 agonists were not taken by any of the patients (LABAs). Adherence to evidence-based recommendations by prescribers was insufficient. Employment position and drug usage in social situations were linked to positive treatment outcomes. In order to increase adherence to evidence-based recommendations, efforts should be directed toward educating patients and healthcare professionals about the current recommendations for the management of asthma. For long-term asthma symptom control, a combination of long-acting B2 agonists and inhaled corticosteroids should be promoted.